Unusual case of mobile phone simulation SIM card’s outer case ingestion: wedged at laryngeal surface of epiglottis - Dhingra, Rachna; Davessar, Jai Lal; Sharma, Shruti; Kaur, Kanwalpreet (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Accidental ingestion of foreign bodies in the pediatric population is usually small pieces from toys or other household objects and subsequent emergency department attendance is a common occurrence. Here we describe an unusual case of accidental swallowing where the foreign body is outer case of mobile phone simulation (SIM) card.